Forging Cohesive Societies – Singapore’s Multiracialism : A Matter of Identity - Han, Fook Kwang (2019)
Singapore’s commitment to multiracialism and inter-faith harmony is not just about keeping the peace but about its identity as a nation. It has achieved much over the last 50 years but serious challenges remain. The speed in which fake news and hate speech are spread online can easily create enmity among the races and religious groups. Much depends on whether Singaporeans are merely tolerant of each other or have developed deep trust and understanding.